2000
DOI: 10.4315/0362-028x-63.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Heat Inactivation of Hepatitis A Virus in Dairy Foods

Abstract: Experiments were performed to determine the thermal resistance of hepatitis A virus (HAV) in three types of dairy products containing increased amounts of fat content (skim milk, homogenized milk; 3.5% MFG, and table cream; 18% MFG). HAV-inoculated dairy products were introduced into custom-made U-shaped microcapillary tubes that in turn were simultaneously immersed in a waterbath, using custom-made floating boats and a carrying platform. Following exposure to the desired time and temperature combinations, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 17 publications
4
54
0
Order By: Relevance
“…Our finding in the present study that NoV survival on turkey was slightly greater than that on lettuce suggests that the food surface may affect the persistence of NoV infectiousness or recovery of the virus by elution. This protective effect of food matrices has already been reported for other studies (4,28,34). As found by Mattison et al (28), the smallest reduction in the FCV titer over 7 days at refrigeration temperature was observed for ham, compared to lettuce, strawberries, and stainless-steel surfaces.…”
Section: Discussionsupporting
confidence: 69%
“…Our finding in the present study that NoV survival on turkey was slightly greater than that on lettuce suggests that the food surface may affect the persistence of NoV infectiousness or recovery of the virus by elution. This protective effect of food matrices has already been reported for other studies (4,28,34). As found by Mattison et al (28), the smallest reduction in the FCV titer over 7 days at refrigeration temperature was observed for ham, compared to lettuce, strawberries, and stainless-steel surfaces.…”
Section: Discussionsupporting
confidence: 69%
“…Remarkably, Slomka and Appleton (39) reported a comparable 3 D inactivation in 0.5 to 1 min of FeCV in contaminated cockles at 80°C, indicating that FeCV, unlike hepatitis A virus (2,29), is not significantly stabilized by factors such as fat and high protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix-derived protective effects have been described in connection with heat treatments. An increase in the fat content of milk appeared to have a protective effect on HAV, increasing its heat stability (15,78). In this study, clear protective effects on NV were observed for some heat treatments with various intensities.…”
Section: Discussionmentioning
confidence: 56%
“…Such studies are limited mainly to shellfish (42, 43) and berries (18,19) or to cultivable enteric viruses, such as hepatitis A virus (HAV) (15,24,42,66,78), poliovirus (PV) (26, 84), or rotavirus (12). Due to the lack of a mammalian cell culture or animal model for norovirus, various studies of persistence and inactivation have been performed with genetically related surrogates of norovirus, including feline calicivirus (FCV) (17,28,32,35,68,82,86) and murine norovirus (MNV) (7,8,10,11,21,51), which are cultivable nonenveloped viruses belonging to the family Caliciviridae.…”
mentioning
confidence: 99%